Effects of periconceptional folate on cognition in children of women with epilepsy: NEAD study. (18th February 2020) - Meador, Kimford J.; Pennell, Page B.; May, Ryan C.; Brown, Carrie A.; Baker, Gus; Bromley, Rebecca; Loring, David W.; Cohen, Morris J.
Abstract : Objective: Emerging evidence suggests potential positive neuropsychological effects of periconceptional folate in both healthy children and children exposed in utero to antiseizure medications (ASMs). In this report, we test the hypothesis that periconceptional folate improves neurodevelopment in children of women with epilepsy by re-examining data from the Neurodevelopmental Effects of Antiepileptic Drugs (NEAD) study. Methods: The NEAD study was an NIH-funded, prospective, observational, multicenter investigation of pregnancy outcomes in 311 children of 305 women with epilepsy treated with ASM monotherapy. Missing data points were imputed with Markov chain Monte Carlo methods. Multivariate analyses adjusted for multiple factors (e.g., maternal IQ, ASM type, standardized ASM dose, and gestational birth age) were performed to assess the effects of periconceptional folate on cognitive outcomes (i.e., Full Scale Intelligence Quotient [FSIQ], Verbal and Nonverbal indexes, and Expressive and Receptive Language indexes at 3 and 6 years of age, and executive function and memory function at 6 years of age). Results: Periconceptional folate was associated with higher FSIQ at both 3 and 6 years of age. Significant effects for other measures included Nonverbal Index, Expressive Language Index, and Developmental Neuropsychological Assessment Executive Function at 6 years of age, and Verbal Index and Receptive Language Index at 3 years of age. Nonsignificant effects included Verbal Index, Receptive Index, Behavior Rating Inventory of Executive Function–Parent Questionnaire Executive Function, and General Memory Index at 6 years of age, and Nonverbal Index and Expressive Index at 3 years of age. Conclusions: Use of periconceptional folate in pregnant women with epilepsy taking ASMs is associated with better cognitive development. ClinicalTrials.gov identifier: NCT00021866.